2022
DOI: 10.1021/acs.joc.2c01825
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Access to Carbazole-1,3-dicarbonitrile: A Thermally Activated Delayed Fluorescent (TADF) Photocatalyst for Cobalt-Mediated Allylations

Abstract: The stability of a photocatalyst under irradiation is important in photoredox applications. In this work, we investigated the stability of a thermally activated delayed fluorescence (TADF) photocatalyst {3DPAFIPN [2,4,-5-fluoroisophthalonitrile]}, recently employed in photoredox-mediated processes, discovering that in the absence of quenchers the chromophore is unstable and is efficiently converted by irradiation with visible light into another species based on the carbazole-1,3-dicarbonitrile moiety. The new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…18 After βdeprotonation, intermediate 11 evolves into the 5πe − -activated radical 12, which is then trapped by the ketone-or iminederived radical anion (13)�generated by the reaction of ketone or imine with PC •− exploiting proton-coupled electron transfer 19 �to afford the reaction product (3 or 4). A similar scenario also emerged from the Stern−Volmer experiment run with 5CzBN�one of the best performing dyes in the β-aldol condensation with alkyl-aryl ketones 20 �in acetonitrile (see Figure S3 and Scheme S1 in the Supporting Information). Notably, the k q values of PC's prompt fluorescence quenching by DABCO (see Figure S4 and Table S7 in the Supporting Information) were found to be substantially similar to those of delayed fluorescence, which is in keeping with the fact that reaction yields are only moderately affected by the presence of air (see above).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18 After βdeprotonation, intermediate 11 evolves into the 5πe − -activated radical 12, which is then trapped by the ketone-or iminederived radical anion (13)�generated by the reaction of ketone or imine with PC •− exploiting proton-coupled electron transfer 19 �to afford the reaction product (3 or 4). A similar scenario also emerged from the Stern−Volmer experiment run with 5CzBN�one of the best performing dyes in the β-aldol condensation with alkyl-aryl ketones 20 �in acetonitrile (see Figure S3 and Scheme S1 in the Supporting Information). Notably, the k q values of PC's prompt fluorescence quenching by DABCO (see Figure S4 and Table S7 in the Supporting Information) were found to be substantially similar to those of delayed fluorescence, which is in keeping with the fact that reaction yields are only moderately affected by the presence of air (see above).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cozzi et al later successfully replaced the expensive Irphotocatalyst with organic dye for the cobalt-mediated allylation of aldehydes (Scheme 59). [55] The authors showed that the photoconversion of commercial 3DPAFIPN photocatalyst provided catalyst PC (2DPAPhCzDCN), which was applicable for the Co-promoted allylation of aldehydes (Scheme 59). Using a Hantzsch ester as the terminal reductant, various (hetero)aromatic aldehydes were successfully allylated in moderate yield.…”
Section: Reaction With Aldehydes and Ketonesmentioning
confidence: 99%
“…TADF compounds have been studied as energy transfer photocatalysts as well as electron transfer (photo redox) catalysts in recent years based on their triplet state energy levels and excited state redox potentials of PC and substrates. [11,[17][18][19][20][21] The most well-studied D-A TADF material based on carbazole donor and dicyanobenzene acceptor 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN), has been extensively utilized in photocatalysis due to its long-lived triplet state (1.3 μs), suitable redox potentials and similar properties as Iridium (Ir) based photocatalysts. [11,13,21] In 2016, Luo and Zhang reported 4CzIPN as photocatalyst for dual catalyzed cross-coupling reaction for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Upon visible light photoexcitation, PC is photoexcited and can interact with organic substrates either through energy transfer (PEnT) or electron transfer (PET) processes. TADF compounds have been studied as energy transfer photocatalysts as well as electron transfer (photo redox) catalysts in recent years based on their triplet state energy levels and excited state redox potentials of PC and substrates [11,17–21] . The most well‐studied D‐A TADF material based on carbazole donor and dicyanobenzene acceptor 1,2,3,5‐tetrakis(carbazol‐9‐yl)‐4,6‐dicyanobenzene (4CzIPN), has been extensively utilized in photocatalysis due to its long‐lived triplet state (1.3 μs), suitable redox potentials and similar properties as Iridium (Ir) based photocatalysts [11,13,21] .…”
Section: Introductionmentioning
confidence: 99%